The 2019 super-Eddington outburst of RX J0209.6-7427: detection of pulsations and constraints on the magnetic field strength - Vasilopoulos, G.; Ray, P. S.; Gendreau, K. C.; Jenke, P. A.; Jaisawal, G. K.; Wilson-Hodge, C. A.; Strohmayer, T. E.; Altamirano, D.; Iwakiri, W. B.; Wolff, M. T.; Guillot, S.; Malacaria, C.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
In 2019 November, MAXI detected an X-ray outburst from the known Be X-ray binary system RX J0209.6-7427 located in the outer wing of the Small Magellanic Cloud. We followed the outburst of the system with NICER, which led to the discovery of X-ray pulsations with a period of 9.3 s. We analysed simultaneous X-ray data obtained with NuSTAR and NICER, allowing us to characterize the spectrum and provide an accurate estimate of its bolometric luminosity. During the outburst, the maximum broad-band X-ray luminosity of the system reached (1-2) × 1039 erg s-1, thus exceeding by about one order of magnitude the Eddington limit for a typical 1.4 M⊙ mass neutron star (NS). Monitoring observations with Fermi/GBM and NICER allowed us to study the spin evolution of the NS and compare it with standard accretion torque models. We found that the NS magnetic field should be of the order of 3 × 1012 G. We conclude that RX J0209.6-7427 exhibited one of the brightest outbursts observed from a Be X-ray binary pulsar in the Magellanic Clouds, reaching similar luminosity level to the 2016 outburst of SMC X-3. Despite the super-Eddington luminosity of RX J0209.6-7427, the NS appears to have only a moderate magnetic field strength.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; galaxies: individual: SMC; pulsars: individual: RX J0209.6-7427; stars: neutron; X-rays: binaries